Identifying Latent Profiles of Healthy Adults’ Biopsychosocial Pain Concepts - Catherina Lenhof; Laura Dukek; Linda Wickering; Lena Hitschler; Michael Schneider; Tanja Hechler (Pain Research and Management)
Discussion: Results provide preliminary evidence for distinct profiles of biopsychosocial pain concepts among healthy adults. Further research should replicate these findings in clinical samples to better understand biopsychosocial pain concepts and their use for individualized pain science education.